The chromosomes and the sex determining mechanism of Scaphura nigra (Orthoptera, Ensifera, Tettigoniidae, Phaneropterinae). - Mesa, Alejo; Fontanetti, Carmem Silvia; Ferreira, Amilton (Pensoft Publishers, 2010)
Scaphum nigra has a uniquechromosomecomplement among approximately 100 species studied so far belonging to the subfamily Phaneropterinae. It is formed by 2n ([male]) = 26 and a FN = 29 and derived from the ancestral karyotype of the group 2n ([male]) = 31, FN = 31, by means of two centric fusions and one tandem fusion. The first between the X chromosome and a medium-sized autosome giving rise to a neo-XY sex chromosome mechanism of recent origin, and the second between two acrocentric ones, the bigger and a medium size, that gave rise to a large submetacentric element whose length is very uncommon in the subfamily. This process has created a bimodal karyotype that contrasts with the majority in this group, whose chromosomes usually can be arranged in a decreasing order of size. A third rearrangement incorporating the chromatin of a medium-sized autosome to the bigger one, explains the reduction observed in the number of chromosomes and the enlarged size of the submetacentric elements. These features demonstrate the effectiveness of chromosome number, their morphology and the change of the sex mechanism as useful tools for taxonomy.